Perbaikan Faktor Daya Pada Instalasi Listrik 3 Phasa Pabrik Refill Oksigen Kapasitas 105 kVA dengan Pemasangan Panel Kapasitor Bank - Akhdiyatul Akhdiyatul (Electrical Network Systems and Sources, 2022)
Electrical loads have resistive, inductive and capacitive characteristics. This characteristic will have an impact on the electrical system, namely the power factor. The power factor value is limited from 0 to 1. If the power factor value is close to 1 (high active power), the electrical system will be better, and vice versa, if the power factor is low, it is close to 0 (high reactive power), so that less electrical power can be utilized from the amount of power looks the same. When the electrical system has a low power factor (large reactive power) it will affect the decrease in power quality and increase the use of electric power. In problem identification, it is found that there is a lot of use of electro motors or 3 phase electric motors which produce inductive loads and affect the power factor or cos phi. PLN has determined the minimum value of the power factor is 0.8. If the power factor is below 0.8 then consumers or factories that use it will be fined by PLN. The need for a capacitor bank that is used at a power capacity of 105 kVA with a cos phi of 0.9 is 22.33 kVAR.